Nociceptor-Dependent Locomotor Dysfunction After Clinically-Modeled Hindlimb Muscle Stretching in Adult Rats with Spinal Cord Injury. - Keller, Anastasia V. (Exp Neurol, 2019)
In the course of investigating how common clinical treatments and adaptive technologies affect recovery after spinal cord injury (SCI), we discovered that a clinically-modeled hindlimb stretching protocol dramatically, but transiently, reduces locomotor function. Nociceptive sensory input is capable of altering motor output at the spinal level, and nociceptive neurons are sensitized after SCI. Here we tested the hypotheses that stretch-induced locomotor deficits are dependent on nociceptive afferents by depleting TRPV1+ sensory afferents using capsaicin injections in neonatal rats. Following maturation, animals received 25g-cm contusive SCI at T10. After plateau of locomotor recovery at 6 weeks, daily stretching was performed for 3 weeks, followed by 2 weeks without stretch, and again for two additional weeks. Animals were sacrificed 2h after the last stretching session for histological assessments. Consistent with previous findings, stretch-induced drops in locomotor function were observed in nociceptor-intact animals but were nearly absent in nociceptor-depleted animals. These functional changes were accompanied by corresponding increases in the number of c-Fos+ nuclei throughout the lumbar enlargement. As expected, nociceptor-depleted animals had very little CGRP+ axonal innervation of the dorsal horn. Nociceptor-intact stretched animals had significantly higher levels of CGRP+ as compared to non-stretched SCI rats, suggesting that stretching promoted intraspinal CGRP+ sprouting. These results indicate that stretch-induced locomotor dysfunction in animals with incomplete SCI involves C-fibers, adding a negative post-SCI role to their adaptive roles (e.g., bladder control), and suggesting that the clinical use of muscle stretching to combat contractures and spasticity may be unintentionally detrimental to locomotor function.